2009
DOI: 10.1093/rpd/ncp264
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric survey of teletherapy treatment rooms in Brazil

Abstract: The Brazilian national regulatory authority, National Commission of Nuclear Energy, requires that dose rates in the vicinity of teletherapy treatment rooms do not exceed the permissible limits for workers as well as members of the public, depending on the place considered. At the end of 2005, the Brazilian national regulatory authority reduced the permissible dose limit for controlled areas from 1000 to 400 microSv week(-1). Therefore, the aim of this work is to verify the adequacy of structural shielding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Survey monitoring audits indicated that the most critical noncompliances were observed in uncontrolled areas in the vicinity of 60Co facility rooms where measured dose rates values like 0.55 and 4.5 mSv/week, (as reported (21) ), were obtained. In many cases the facilities were subjected to nonauthorized project changes, or the person responsible for the facility decided to utilize a higher activity 60Co source not appropriate to the existing approved irradiator bunker shielding .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Survey monitoring audits indicated that the most critical noncompliances were observed in uncontrolled areas in the vicinity of 60Co facility rooms where measured dose rates values like 0.55 and 4.5 mSv/week, (as reported (21) ), were obtained. In many cases the facilities were subjected to nonauthorized project changes, or the person responsible for the facility decided to utilize a higher activity 60Co source not appropriate to the existing approved irradiator bunker shielding .…”
Section: Resultsmentioning
confidence: 96%
“…In many cases the facilities were subjected to nonauthorized project changes, or the person responsible for the facility decided to utilize a higher activity 60Co source not appropriate to the existing approved irradiator bunker shielding . ( 21 ) Another possible reason is a 60Co unit was positioned at an unusual configuration (for instance, forming angles about 45° with the bunker walls), a situation that can generate higher dose rates in the neighborhood of the treatment room (22) …”
Section: Resultsmentioning
confidence: 99%
“…In Brazil this has been carried out since several decades by Brazilian Nuclear Regulatory Authority (CNEN). The methodology used in this radiometric survey is to measure the instantaneous dose-equivalent rate in Sv/h at strategic points and calculate the weekly rate through a simple equation that involves the weekly workload W (equation (5) below, see for example [1]).…”
Section: Introductionmentioning
confidence: 99%
“…1. Method 1 (historical old method) Radiometric surveys in radiotherapy bunkers have been doing for a long time by measuring only I T , both before the advent of the IMRT technique and after the incorporation of this technique, so that the total weekly dose-equivalent rate, call it R…”
mentioning
confidence: 99%